Development of an in vitro metabolic dysfunction-associated steatohepatitis model to investigate altered drug metabolizing enzymes, transport proteins, and hepatobiliary disposition - Murphy, William A.; Kyburz, Sarina; Ho, Henry; Loop, Matthew Shane; Fallon, John K.; Tiley, Jacqueline B.; Kralj, Thomas; Brouwer, Kim L. R. (Frontiers in Pharmacology, 2026)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) is estimated to affect ∼30% of adults globally. The progressive form of MASLD, metabolic dysfunction-associated steatohepatitis (MASH), is a leading cause of chronic liver disease. MASH is marked by hepatocellular fat accumulation (steatosis), ballooning, and inflammation. Although many in vitro and in vivo models replicate MASH pathophysiology, no in vitro hepatocyte MASH model has been evaluated for its ability to reflect clinically observed changes in drug metabolizing enzymes (DMEs) and transporters. In this study, we addressed this gap by developing a model using sandwich-cultured human hepatocytes (SCHH) that mimics both MASH pathophysiology and alterations in DME and transporter concentrations and function.MethodsLipid–cytokine treatments were first optimized using differentiated HuH-7 cells based on cellular toxicity and their ability to induce a MASH-like phenotype. Three final treatments—all including TNF-α (1 ng/mL) and IL-6 (1.2 ng/mL)—were selected for SCHH evaluation: (1) oleic acid (OA):palmitic acid (PA) (1:2, 0.5 mM), (2) a lipid mix (lysophospholipids mixture + OA:PA), and (3) lipid mix + 0.01 mM cholesterol. Treatments were incubated for 72 h with SCHH from three donors. Quantitative targeted absolute proteomics (QTAP) assessed the transporter and DME concentrations, whereas B-CLEAR® technology evaluated transporter function using the probe substrates [3H]-taurocholate (TCA) and [3H]-estradiol-17β-glucuronide (E217G).ResultsAll three treatments significantly increased lipid droplet formation and peroxidation in SCHH with minimal toxicity. These treatments also altered DME and transporter concentrations in a manner similar to the changes observed in liver tissue from patients with MASH. Across treatments, concentrations of the bile salt export pump (BSEP), sodium taurocholate co-transporting polypeptide (NTCP), organic anion transporting polypeptide (OATP) 1B1, OATP1B3, and multidrug resistance-associated protein (MRP) 2 were reduced by 0.66–0.57-fold, 0.71–0.52-fold, 0.74–0.63-fold, 0.82–0.80-fold, and 0.71–0.48-fold, respectively. Correspondingly, the TCA apparent uptake clearance and biliary clearance were reduced by 0.70–0.26-fold and 0.61–0.27-fold, respectively. E217G apparent uptake clearance was reduced by 0.67–0.35-fold, whereas biliary excretion index values were reduced to negligible levels.DiscussionThese findings demonstrate that lipid–cytokine treatments induce MASH-like changes in SCHH, including clinically relevant reductions in DME and transporter concentrations and function. This model may serve as a valuable tool for predicting altered hepatobiliary drug disposition in MASH.